Phenotypic Stability of Drought Index in Pearl Millet - Sagar, P; Kapoor, R L; Jatasara, D S (Annals of Arid Zone, 2016)
Phenotypic stability of drought index in pearl millet was investigated by . growing 80 genotypes (parents,F, hybrids,checks) in six environments including four water stress conditions. G x E (linear) interactions showed significant differences indicating that performance of the genotypes in stress conditions could be predicted. Three crosses i.e. 1027-P. x HS-1-71-2-2-P2, 78/838-7 x HS-1-71-2-2-P2 and 5054 B x HS-1-71-2-2-P2 were identified as the best hybrids for drought index and these can be used in the breeding programme for evolving drought tolerant cultivars of the pearl millet.